Menanamkan Nilai Kewirausahaan Melalui Kegiatan Berkebun di TK Tarbiyatul Athfal II Kawak - Purwanti, Indah (CV. Supernova Office Stationary and Printing, 2023)
The cultivation of entrepreneurial character needs to: be given from an early age according to the stage of child development so that entrepreneurial character will be more easily embedded and internalized in children. Early childhood is a critical period of human development where all potential can be developed optimally through proper stimulation and education, and this builds a strong foundation for success as an adult. The approach used in this research is a literature study. Literature study is a technique in data collection. Data analysis is by examining journals, literature, notes, books and various sources relating to the problem to be studied and solved. The focus of cultivating entrepreneurial character is not teaching children to make money or trading from an early age, but building character and developing skills so that when they grow up they are ready and have the skills to become entrepreneurs. Through the use of school gardens, students are expected to have a better understanding of the origins of healthier food and patterns. Utilization of school gardens is able to provide access to students to learn entrepreneurship.